SRAP as an informative molecular marker to study the Fusarium Poae genetic variability - Dinolfo, María Inés (2015)
Fusarium poae is one of the Fusarium species isolated from grains associated with Fusarium Head Blight (FHB), whose occurrence has increased in the last years. In this study, a total of 105 F. poae isolates from Argentina, Belgium, Canada, England, Finland, France, Germany, Hungary, Italy, Luxembourg, Poland, Switzerland and Uruguay were evaluated by using sequence-related amplified polymorphism (SRAP) to analyze the capacity of this molecular marker to evaluate the F. poae genetic variability. The molecular analysis showed high intraspecific variability within F. poae isolates and a partial relationship was revealed between variability and the host/geographic origin. Analysis of molecular variance (AMOVA) indicated a high genetic variability in the F. poae collection, with most of the genetic variability resulting from differences within, rather than between American and European populations. The analysis of sequenced SRAP fragments targets into hypothetical proteins from different Fusarium species showing that the SRAP technique not only allows studying F. poae genetic variability, but also targets coding regions into the F. poae genome. To our knowledge this is the first report on genetic variability of F. poae using SRAP technique and also demonstrates the efficacy of this molecular marker to amplify open reading frames in fungus.